Something More Splendid Than Two - Alfaro, Jose (punctum books, 2022)
Blending literary analysis and memoir, Something More Splendid Than Two is at once an excavation of intergenerational wounds, a dance number, a poem, and a fraught love letter from son to father that disrupts the dominant narratives surrounding the life and myth of Joaquín Murrieta. In the Mexican American imaginary, the legend of Joaquín Murrieta has been recast to explain the wounding of Mexican American men after the 1848 border formation. In these versions, Joaquín is a vigilante hero and the patriarchal father of the Chicanx movement. Revisiting the most circulated version of the Joaquín myth, The Life and Adventures of Joaquín Murieta written by Cherokee writer John Rollin Ridge, the first published Native American author in the US, Something More Splendid Than Two offers an alternative to these versions. Stitching together multiple tangled histories of Indigenous and Mexican woundings living in the margins of Ridge's 19th-century novel, alfaro opens a queer timeline where Chicanx and Indigenous solidarities can be imagined. By attuning to the choreographies of power and patriarchy that produced readers and writers like Ridge and the author of this book, josé rivers alfaro imagines that in that endless encounter between reader and writer, both time travel and collective healing are possible.